Analisis Penerapan Penyusunan Laporan Keuangan Berdasarkan Pedoman Akuntansi Pesantren Pada Pondok Pesantren Nurul Haq Desa Rangkiling - Pelita Hati Harapan Jaya; Usdeldi Usdeldi; Marissa Putriana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine and analyze the recording of financial reports at the Nurul Haq Islamic boarding school in accordance with Islamic boarding school accounting guidelines which include financial position reports, net asset change reports, cash flow reports and notes to financial reports. The method used in this research is qualitative with a descriptive approach. The results of this research found that currently the Nurul Haq Islamic boarding school only uses simple financial reports because it does not fully understand Islamic boarding school accounting guidelines, due to a lack of knowledge and information regarding Islamic boarding school accounting.